(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This article systematically analyzes the origin, development, and architectural and engineering features of defensive structures integral to the ancient historical cities of Central Asia. The study provides a comparative study of the unique defensive systems of the oases of Sogdiana, Bactria, and Khorezm. In light of the improvements in military defense, the reasons for the development of the architecture of city walls, towers, moats, and arches constructed of pakhsa and mud brick are explored.